Microbiological attributes and performance of the bacterial community in brazilian cerrado soil with different cover crops - de Lima, Sebastião Ferreira; Secco, Vinicius Andrade; Simon, Cátia Aparecida; Silva, Antônio Marcos Miranda; Vendruscolo, Eduardo Pradi; Andrade, Maria Gabriela de Oliveira; Contardi, Lucymara Merquides; de Lima, Ana Paula Leite; Cordeiro, Meire Aparecida Silvestrini; Abreu, Mariele Silva (MDPI, 2021)
Soil microbiological indicators are essential tools to understand how the management with cover crops interferes in the activity and the soil microbial community. Thus, the objective of the study was to evaluate microbiological attributes and performance of the bacterial community in the soil of the Brazilian Cerrado with different cover crops. The experiment was performed in a randomized block design, evaluating seven cover crops, Sorghum bicolor, Crotalaria ochroleuca, Pennisetum americanum, Panicum miliaceum, Raphanus sativus, Urochloa brizantha, Urochloa ruziziensis, and a fallow area. Cover aerial biomass dry weight (CB), microbial biomass carbon (MBC), basal soil respiration (BR), metabolic quotient (qCO2 ), and abundance and structure of bacterial community based on the rrs 16S rRNA gene were evaluated. In the soil cultivated with S. bicolor there was the highest CB and MBC at the same time as there was less microbial activity (lower BR and qCO2 ). The structure of the bacterial community was more differentiated in soils cultivated with S. bicolor, P. americanum, and C. ochroleuca. The MBC was more associated with cover crops of the Urochloa genus, while BR was positively correlated with S. bicolor. Bacterial abundance was positively correlated with P. miliaceum.
Keywords: Microbial activity; No-till; Organic carbon; Soil quality